Genome-wide identification, characterization, and expression analysis of the SWEET gene family in cucumber - Li-ping HU; Feng ZHANG; Shu-hui SONG; Xiao-wei TANG; Hui XU; Guang-min LIU; Yaqin WANG; Hong-ju HE (Journal of Integrative Agriculture, 2017)
SWEETs (sugars will eventually be exported transporters) are a novel class of recently identified sugar transporters that play important roles in diverse physiological processes. However, only a few species of the plant SWEET gene family have been functionally identified. Up till now, there has been no systematic analysis of the SWEET gene family in Cucurbitaceae crops. Here, a genome-wide characterization of this family was conducted in cucumber (Cucumis sativus L.). A total of 17 CsSWEET genes were identified, which are not evenly distributed over the seven cucumber chromosomes. Cucumber SWEET protein sequences possess seven conserved domains and two putative serine phosphorylation sites. The phylogenetic tree of the SWEET genes in cucumber, Arabidopsis thaliana, and Oryza sativa was constructed, and all the SWEET genes were divided into four clades. In addition, a number of putative cis-elements were identified in the promoter regions of these CsSWEET genes: nine types involved in phytohormone responses and eight types involved in stress responses. Moreover, the transcript levels of CsSWEET genes were analyzed in various tissues using quantitative real-time polymerase chain reaction. A majority (70.58%) of the CsSWEET genes were confined to reproductive tissue development. Finally, 18 putative watermelon ClaSWEET genes and 18 melon CmSWEET genes were identified that showed a high degree of similarity with CsSWEET genes. The results from this study provided a basic understanding of the CsSWEET genes and may also facilitate future research to elucidate the function of SWEET genes in cucumber and other Cucurbitaceae crops.